2018
DOI: 10.3758/s13428-018-1056-1
|View full text |Cite
|
Sign up to set email alerts
|

The Massive Auditory Lexical Decision (MALD) database

Abstract: The Massive Auditory Lexical Decision (MALD) database is an end-to-end, freely available auditory and production data set for speech and psycholinguistic research, providing time-aligned stimulus recordings for 26,793 words and 9592 pseudowords, and response data for 227,179 auditory lexical decisions from 231 unique monolingual English listeners. In addition to the experimental data, we provide many precompiled listener- and item-level descriptor variables. This data set makes it easy to explore responses, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 65 publications
3
106
0
Order By: Relevance
“…Pseudoword data was obtained from the MALD database (Tucker et al, 2018). This database provides auditory lexical decision responses to 26,793 words and 9,592 pseudowords, collected from 231 monolingual English listeners, aged 17-29.…”
Section: The Mald Datamentioning
confidence: 99%
“…Pseudoword data was obtained from the MALD database (Tucker et al, 2018). This database provides auditory lexical decision responses to 26,793 words and 9,592 pseudowords, collected from 231 monolingual English listeners, aged 17-29.…”
Section: The Mald Datamentioning
confidence: 99%
“…Another study that implemented LDL to generate the estimated semantic vectors of non-words is Chuang et al (submitted). By examining the acoustic durations and the response times of about 10 thousand auditory non-words in the Massive Auditory Lexical Decision (MALD) database (Tucker et al, 2018), they showed that the semantics of non-words influences the processing of auditory non-words to a substantial extent. Taken together, both the present study and Chuang et al (submitted) 12 See also the work by Hendrix presented at the 11 th International Conference on the Mental Lexicon in which FastText (Bojanowski, Grave, Joulin, & Mikolov, 2016) is used to generate semantic vectors for non-words and semantic neighborhood density is found to reliably predict reaction times in a lexical decision task.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure might occasionally result in unreasonably long word length estimations (e.g., because of a long dramatic pause between words). In such cases, we used a word truncation algorithm based on mean word lengths in conversational speech 65 . A more detailed account of how this script works is available in the Supplementary Materials.…”
Section: Movie Annotationsmentioning
confidence: 99%